IDEOLOGI PENERJEMAH DALAM TERJEMAHAN KATA TABU PADA FILM 22 Jump Street - Muhammad - Arif; M.R. Nababan; Riyadi Santosa (Linguistik Indonesia, 2019)
This research aims to discover the ideology of the translator in translating taboo words in 22 Jump Street movie by doing qualitative research. In order to determine the idology, the researcher follows some steps that are collecting linguistics data by using criterion-based sampling technique to find out the taboo words and their categories, and then collecting translation data by using content analysis to figure out translation technique used by the translator therefore the idology will be able to determine. The result of this research discovers that the ideology of the translator is domestication determined from the tendency of translator to delete taboo words in his translation and to find the equivalence of taboo words in target language at the same time.